A survey of northern Victorian dairy farmers to investigate dairy calf management: calf‐rearing practices. Issue 4 (25th March 2018) - Phipps, AJ; Beggs, DS; Murray, AJ; Mansell, PD; Pyman, MF
Abstract : Objectives: To describe the calf‐rearing practices carried out in northern Victorian dairy herds and to identify weaknesses that may affect calf health and welfare by comparing the results with current industry recommendations. Methods: Survey of dairy farms from Rochester and the surrounding farming area. Results: The response rate was 39% (58/150). Many dairy producers were not meeting the current industry recommendations in the following areas: (1) delayed access to pellets and roughage, (2) failing to provide access to water from birth, (3) delayed disbudding of calves, (4) delayed timing of booster vaccinations, (5) weaning based on age alone, (6) failing to isolate sick calves and (7) early sale age of excess calves. Conclusion: The results from this survey highlight the need for greater awareness of industry standards for calf husbandry and weaning.